Optimum performance of carbon nanotube field effect transistor - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz (2014)
Phenomenological predictions have been elucidated in this paper. The predictions are elaborated for the field effect transistor using carbon nanotube (CNT) technology. CNTs have small band gap compare to other traditional semiconductor technologies. The modeling of a single wall nanotube with optimum bandgap for the designing of the carbon nanotube (CNTFET) is the aim of this work. Analysis of I-V characteristics of CNTFET with the drain current-voltage analytical relation enables the lower energy consumption from the proposed design. In this research, the optimum carbon nanotube (CNTs) is analyzed where the bandgap is 0.45eV as well as the diameter is 1.95nm. Modeling of CNTFET will be useful for semiconductor industries in order to manufacture the nano scale device.